PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK HALAL YANG DIMEDIASI OLEH MINAT BELI - Antik Kristyaningsih; Bayu Kurniawan; Heri Prabowo (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The growth of the halal cosmetics industry in Indonesia is predicted to continue to increase in line with product innovation, changes in consumer preferences and technological advances in this field. Promotion and product quality is a marketing strategy that can stimulate buying interest before consumers finally make a purchasing decision.This research aims to analyze the influence of promotion and product quality on purchasing decisions for halal cosmetics, with purchase interest as a mediating variable. The object of this research is Wardah cosmetics users in Semarang City, with a sample size of 170 respondents. Data processing was carried out using the Structural Equation Model (SEM) method which was analyzed using the AMOS 24 application. The results of hypothesis testing show that promotional variables and product quality do not have a direct influence on purchasing decisions. However, the purchase interest variable is proven to have a significant influence on purchasing decisions. In addition, the promotion variable does not influence purchasing interest, while the product quality variable significantly influences purchasing interest. The mediation test shows that promotions do not influence purchasing decisions through purchasing interest, while product quality has a significant influence on purchasing decisions through purchasing interest.